Pengaruh Pengembangan Pegawai dan Motivasi Intrinsik Terhadap Kinerja Pegawai di Kantor Desa Sukaramai Kec. Muara Tembesi, Kab. Batanghari - Asha Zabirra; Sumarni Sumarni; Fitri Widiastuti (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to examine and analyze the influence of employee development and intrinsic motivation on employee performance at the Sukaramai Village Office, Muara Tembesi District, Batanghari Regency. The research used is quantitative research with a descriptive-verificative approach. The sample consisted of 30 respondents who are employees of the Sukaramai Village Office. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the aid of SPSS version 27. The results indicate that, individually, employee development (X1) has a positive and significant effect on employee performance (Y) with a significance value < 0.05. Similarly, intrinsic motivation (X2) has a positive and significant effect on employee performance with a significance value < 0.05. Simultaneously, both variables have a significant effect on employee performance. The results of this study indicate that the better the employee development and the higher the intrinsic motivation possessed, the better the employee performance at Sukaramai Village Office will be.